Blockchain Enabled Tracking of Physician Burnout and Stressors During the COVID-19 Pandemic - Dhillon, Vikram; Xu, Tailong; Parikh, Chirag (Frontiers in Blockchain, 2021)
With more than 54 million cases worldwide, the novel coronavirus disease 2019 (COVID-19) has disrupted every aspect of public life and poses an ever-growing burden on an already strained healthcare system. The emergence of new COVID-19 hot-spots and super-spreader events are placing an immense amount of stress on hospital systems responding to the increased influx of critically-ill patients. Healthcare workers and frontline physicians disproportionately bear the additional physical and psychological burdens associated with the appearance of a new hot-spot. However, the mental health implications of COVID-19 for physicians are not well understood. In this perspective piece, we discuss widespread effects of the ongoing pandemic on physician mental health and how blockchain infrastructure can enable digital health technologies in supporting data-driven fatigue mitigation interventions. This is particularly applicable to simplifying physician workflows in newly-emerging hot-spots.